Distribution and abundance of mud crabs (Crustacea: Portunidae) in Pacific and Indian Ocean coasts of Thailand - SOFIYUDIN MAAE; PORNPIMON CHUADUANGPUI; SUKREE HAJISAMAE; PAYAP MASNIYOM; SAWEIT CHAYMONGKOL; SITTHISAK JANTARAT; SUPAPORN SAENGKAEW (Society for Indonesian Biodiversity, 2025)
Abstract. Maae S, Chuaduangpui P, Hajisamae S, Masniyom P, Chaymongkol S, Jantarat S, Saengkaew S. 2025. Distribution and abundance of mud crabs (Crustacea: Portunidae) in Pacific and Indian Ocean coasts of Thailand. Biodiversitas 26: 4534-4544. Mud crabs (Crustacea: Portunidae) are economically important species found in the two oceans of Thailand's coastal waters. This study aimed to examine the species composition and size variation of Scylla species across two distinct coastal regions of Thailand, the Gulf of Thailand (GOT, Pacific Ocean) and the Andaman Sea (ADM, Indian Ocean), and to contextualize these findings within global distribution patterns. A total of 4,116 specimens were collected from five sampling sites during June 2022 and June 2023. Carapace Width (CW) and Body Weight (BW) were recorded for each individual. In the GOT, the species composition was dominated by S. olivacea (86.24%), followed by S. paramamosain (11.32%) and S. tranquebarica (2.45%). In the ADM, S. olivacea accounted for 99.40%, and S. paramamosain 0.60%; S. tranquebarica was absent. Size variation analysis showed that both male and female S. olivacea, and female S. paramamosain from the GOT were significantly larger (P<0.05) in CW and BW than those from the ADM. No significant size difference was observed in male S. paramamosain (P>0.05). Monthly data from the GOT revealed peak S. olivacea proportions in January (93.81%), April (91.85%), and June (91.02%); the lowest proportion was observed in June (74.83%). Scylla paramamosain peaked in June (23.18%), followed by February (19.75%) and May (16.00%). Scylla tranquebarica showed low occurrences, peaking in November (6.42%), followed by June (4.19%) and February (3.70%). In the ADM, S. olivacea was consistently dominant. These findings provide baseline data for population assessments, resource management, and aquaculture development, contributing to a broader ecological understanding of economically valuable Scylla species.